Prevalence and Odds of Anxiety Disorders and Anxiety Symptoms in Children and Adults with Psoriasis: Systematic Review and Meta-analysi - Isabelle Jalenques; Fabien Bourlot; Elisa Martinez; Bruno Pereira; Michel D'Incan; Sophie Lauron; Fabien Rondepierre (Medical Journals Sweden, 2022)
The magnitude of the association between psoriasis and depression has been evaluated, but not that between psoriasis and anxiety. The aim of this systematic review and meta-analysis was to examine the prevalence and odds of anxiety disorders and symptoms in patients with psoriasis. Five medical databases (Cochrane Database, EMBASE, PubMed, PsychINFO, ScienceDirect) were searched for relevant literature. A total of 101 eligible articles were identified. Meta-analysis revealed different prevalence rates depending on the type of anxiety disorder: 15% [95% confidence interval [CI] 9-21] for social anxiety disorder, 11% [9-14] for generalized anxiety disorder, and 9% [95% CI 8-10] for unspecified anxiety disorder. There were insufficient studies assessing other anxiety disorders to be able to draw any conclusions on their true prevalence. Meta-analysis also showed a high prevalence of anxiety symptoms (34% [95% CI 32-37]). Case-control studies showed a positive association between psoriasis and unspecified anxiety disorder (odds ratio 1.48 [1.18; 1.85]) and between psoriasis and anxiety symptoms (odds ratio 2.51 [2.02; 3.12]). All meta-analyses revealed an important heterogeneity, which could be explained in each case by methodological factors. The results of this study raise the necessity of screening for the presence of anxiety disorders, as previously recommended for depressive disorders, in patients with psoriasis and, if necessary, to refer such patients for evaluation by a mental health professional and appropriate treatment.